Histopathological Changes in Gallbladder Mucosa in Relation to Gallstone: A Cross-Sectional Study from a Tertiary Care Center - Nepal, Niraj; Bhattarai, Amit; Adhikari, Dinesh (Journal of Nobel Medical College, 2026)
Background: Gallstone disease is common in Nepal, yet the relationship between gallstone characteristics and gallbladder mucosal pathology is not well defined. Materials and Methods: This cross-sectional study included 288 consecutive cholecystectomy specimens from a tertiary care center. Clinical data, gallstone number, size and composition (cholesterol, pigment, mixed) were recorded. Gallbladder mucosa was examined histologically and associations between stone variables and inflammatory, premalignant and malignant lesions were analyzed. Results: The mean age was 44 years with a female-to-male ratio of 2.6:1. Chronic cholecystitis was the predominant lesion (72.9%), while epithelial dysplasia and adenocarcinoma were identified in 2.8% and 1.4% cases, respectively. Mixed stones were most frequent (54.2%), followed by cholesterol (30.9%) and pigment stones (14.9%), with no significant association between stone composition and histological severity (p=0.125). In contrast, multiple stones (72.9%) and larger stones (>20 mm) were significantly associated with advanced inflammatory and neoplastic changes (p<0.001 and p=0.005, respectively). Conclusion: Chronic cholecystitis is the predominant histological pattern in gallstone disease, with mixed stones most common and no significant link between stone composition and mucosal severity, whereas multiple and larger stones are clearly associated with advanced inflammatory and neoplastic changes.